Особливості формування азотвмісного радикала у зразках біогенного гідроксилапатиту за даними ЕПР - Дудченко, Н.О. (Мінералогічний журнал, 2011)
Біогенний гідроксилапатит з кісток корів був підданий термічній обробці в умовах нестачі та надлишку кисню в температурному діапазоні (700, 750, 800, 850, 900 ºC). Показано, що внаслідок термічної обробки біогенного гідроксилапатиту в умовах нестачі кисню у зразках утворюються азотвмісні радикали (NO₄²⁻). В результаті термообробки біогенного гідроксилапатиту в умовах надлишку кисню такі радикали не утворюються. Визначено, що максимальна інтенсивність спектра ЕПР азотвмісних радикалів або їх максимальна кількість спостерігається під час відпалювання за температури 800—850 °С. Зроблено висновок, що даний азотвмісний центр входить до структури біогенного гідроксилапатиту за рахунок ізоморфного заміщення фосфору в структурі гідроксилапатиту на азот (P → N). Отримані результати можуть бути використані під час досліджень механізмів ізоморфних заміщень в апатиті. Биогенный гидроксилапатит из костей коров был подвергнут термической обработке в условиях недостатка и избытка кислорода в температурном диапазоне (700, 750, 800, 850, 900 °С). Показано, что при термообработке биогенного гидроксилапатита в условиях недостатка кислорода в образцах образуются азотсодержащие радикалы (NO₄²⁻). При термообработке его в условиях избытка кислорода такие радикалы не образуются. Показано, что максимальная интенсивность спектра ЭПР азотсодержащих радикалов или максимальное их количество наблюдается при отжиге в температурном диапазоне 800—850 °С. Сделан вывод, что данный азотсодержащий центр входит в структуру биогенного гидроксилапатита за счет изоморфного замещения фосфора в структуре гидроксилапатита азотом (P → N). Полученные результаты могут быть использованы при исследованиях механизмов изоморфных замещений в апатите. The most abundantly produced phosphate mineral in organisms is hydroxylapatite. It is the mineral present in ver tebrate bones and teeth. For the most part, healthy mineralized tissues are hierarchical composites composed principally of carbonate-substituted hydroxylapatite, closely associated with a collagen matrix. Biogenic hydroxylapatite from the bones of cows was exposed to thermal treatment under lack and excess of oxygen in temperature range (700, 750, 800, 850, 900 °С). It was shown, that during thermal treatment of biogenic hydroxylapatite under oxygen lack nitrogen radicals (NO₄²⁻) are formed in the samples. Such radicals don’t formed by thermal treatment of biogenic hydroxylapatite at oxygen excess. It was shown, that maximal intensity of nitrogen radicals ESR spectrum or maximal quantity of nitrogen radicals occurs in temperature range 800—850 °С. It was concluded, that this nitrogen centre is localized in the structure of biogenic hydroxylapatite in phosphorus position due to isomorphous substitution of phosphorus in hydroxylapatite structure by nitrogen (P → N). Obtained results could be useful when studying the mechanisms of isomorphous substitutions in apatite.